2019
DOI: 10.1088/1755-1315/388/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bio fertilizer and magnetic irrigation water on growth and yield of melon Cucumis melo L.

Abstract: The field experiment was conducted at Baqubah nursery, Directorate of Diyala agriculture in Iraq during summer growing of 2017 to study the effect of bio and chemical fertilizers with magnetized water as well as their interactions on growth and yield of melon cv. Piel de sapo. The experiment was laid-out in Randomized Complete Block Design with factorial experiment with three replications and two factors, included two treatments of fertilizer types (urea 50 kg N. ha−1) with Bio-fertilizer (Azospirillum brasile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…When irrigation water is exposed to the magnetic field, it changes its physical, chemical, and electrical properties, which in turn affects its behavior in the plant and the subsequent production characteristics of acidity, conductivity, chemical content, and medicinal activity (Wang et al, 2018;Alavi et al, 2020), therefore modifying the acidity and conductivity of red watermelon juice and increasing its sugar content. This result is consistent with the work of Ali et al (2019), it revealed that the magnetic water treatment excelled in all the studied traits on growth and yield of melon cv. Piel de sapo.…”
Section: The Biochemical Effects Of Magnetically Treated Irrigation W...supporting
confidence: 93%
“…When irrigation water is exposed to the magnetic field, it changes its physical, chemical, and electrical properties, which in turn affects its behavior in the plant and the subsequent production characteristics of acidity, conductivity, chemical content, and medicinal activity (Wang et al, 2018;Alavi et al, 2020), therefore modifying the acidity and conductivity of red watermelon juice and increasing its sugar content. This result is consistent with the work of Ali et al (2019), it revealed that the magnetic water treatment excelled in all the studied traits on growth and yield of melon cv. Piel de sapo.…”
Section: The Biochemical Effects Of Magnetically Treated Irrigation W...supporting
confidence: 93%
“…In addition to research on the efficiency of Azospirillum in promoting plant growth in different culture conditions, the compatibility of its inoculation with other PGPR microorganisms in various crops is also studied, 11,15,[20][21][22][23][24] the influence of the plant genotype, the substances generated in the inoculated plants and their impact on the microbial communities of the soil. [25][26][27] Garcia de Salamone et al, 21 measured the response of three rice cultivars under field conditions inoculated with a commercial formulation of A. brasilense and Pseudomonas fluorescens and evaluated the influence on soil microbial communities through molecular analysis; and concluded that the combined inoculation with A. brasilense and P. fluorescens increased aerial biomass production and grain yield in the three rice cultivars and did not generate a significant impact on soil microbial communities. There are numerous investigations of bipartite inoculations with Azospirillum and rhizobia on leguminous plants with the aim of studying a strategy to improve the sustainability of agricultural production and even highlight the biotechnological potential of secondary metabolites of rhizobia together with inoculants containing rhizobia and A. brasilense to improve the growth and yield of legume and cereal crops such as maize.…”
Section: The Bacterium: Azospirillummentioning
confidence: 99%
“…Irrigation with magnetically treated saline water enhanced plants nutrients N, P, K, Ca, Mg, Fe as compared to normal or untreated saline water [8]. Combination of bio and chemical fertilisers with magnetised water gave highest values of all traits such as fruit yield, fructose content (13.1%), fruit diameter (11.6%), fibre content, fruit firmness (3%) [9]. Germination of seeds increased by 8.34%, average length of root and stem increased by 1 cm and 2.4 cm respectively when compared after 10 days, photosynthetic pigment and protein content showed a significant increase when magnetically treated water was used for irrigation [10].…”
Section: Effect Of Magnetic Treatment On Soil Characteristics and Gro...mentioning
confidence: 99%